2nd International Symposium on portable synchrotron light sources and advanced applications, held in Shiga, Japan 15-17 Januray 2007 - International Symposium on portable synchrotron light sources and advanced applications (2nd : 2007 : Shiga, Japan); Yamada, Hironari editor; Mochchizuku-Oa, Noriko editor?UNAUTHORIZED; Sasaki, Makoto editor?UNAUTHORIZED (Melville, N.Y. : American Institute of Physics, 2007)
This proceedings volume reports the worldwide small light source instrumentation and applications to material and bio-medical sciences. The unique and very sharp x-ray image obtained by MIRRORCLE is demonstrated, and IR synchrotron lights from 10 MeV version makes it possible to study dynamics and behavior of the living specimens in each level such as protein, cell, organ, and whole body.